Effects of redundant visual stimuli on temporal order judgments - Miller, Jeff; Kühlwein, Eva; Ulrich, Rolf (Perception & psychophysics, 2004)
Four experiments were conducted in order to compare the effects of stimulus redundancy on temporal order judgments (TOJs) and reaction times (RTs). In Experiments 1 and 2, participants were presented in each trial with a tone and either a single visual stimulus or two redundant visual stimuli. They were asked to judge whether the tone or the visual display was presented first. Judgments of the relative onset times of the visual and the auditory stimuli were virtually unaffected by the presentation of redundant, rather than single, visual stimuli. Experiments 3 and 4 used simple RT tasks with the same stimuli, and responses were much faster to redundant than to single visual stimuli. It appears that the traditional speedup of RT associated with redundant visual stimuli arises after the stimulus detection processes to which TOJs are sensitive.